Report of the Managing Director to the International Monetary and Financial Committee on IMF Quota and Voice Reform. (Policy Papers; Policy Paper ;, 2006)
The April 2006 Communique of the IMFC called upon the Managing Director to work with the IMFC and the Executive Board to come forward with concrete proposals on IMF quota and voice reform for agreement at the Singapore Annual Meetings in September 2006. An intensive work program on quotas and voice was launched, involving IMF management and staff consultations with a broad spectrum of the membership and discussions in the Executive Board, building on earlier discussions of this issue, including in the context of the IMF's medium-term strategy. Specific reform proposals were discussed on several occasions by the Executive Board, most recently on August 31, 2006. I am pleased that the Executive Board reached agreement on a comprehensive program of reforms, and recommended that the Board of Governors adopt, by September 18, 2006, a resolution that provides for a two-year plan of action.